Flood Disaster Vulnerability Factors in Solok Selatan Regency - Miftahul Jannah; Amsyar Azim Ibrahim (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
ABSTRACT The purpose of this research was to find the vulnerability factors of flood disaster in Solok Selatan Regency. This is a descriptive exploratory research, using primary and secondary survey as methods of data collection. The primary survey was done through semi structured interview with stakeholders, selected from government group. Secondary survey was conducted by institutional survey to obtain a general description of area and flood area in Solok Selatan Regency. To know the vulnerability factors of the floods, the researcher used an analysis technique called content analysis. The result showed that the factors of flood vulnerability in Solok Selatan were: high rainfall, poor drainage condition, slope, factor of road construction vulnerable to water, many meanders, factor of total population affected by floods, siltation caused by waste. Key words : vulnerability factors, flood disaster, Solok Selatan Regency